Effect of chromium supplementation on glucose tolerance in basketball players during competition season - Lee, Y. K.; Chen, C. F.; Chen, M. T.; Su, F. H.; Peng, K. C. (Pre-olympic Congress 2004. Thessaloniki, Grécia. de 6 a 11 de Agosto de 2004, 2004)
The purpose of the study was to determine the effect of oral chromium picolinate on insulin sensitivity in basketball players. The study showed that during competition season chromium picolinate supplementation significantly improved glucose tolerance. It was also found that this improvement was not associated with blood CK and serum cortisol levels.